All Days 2002
DOI: 10.2118/74449-ms
|View full text |Cite
|
Sign up to set email alerts
|

Field Application of Near-Balanced Drilling Using Aqueous Foams in Western Venezuela

Abstract: fax 01-972-952-9435. AbstractThis paper presents operational results of the pilot test under near balanced conditions of a new foam drilling fluid developed by PDVSA-Intevep in an inclined well drilled in La Paz Field in Western Venezuela. The target formations were a fractured, depleted limestone formations of low pressure, and the reservoir contains highly fractured and hard rocks, known for deferred oil production due to flushing by lost circulation. Similar wells drilled with aerated fluids in the vicinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(6)(7)(8) illustrate the effect of well inclination on the cuttings concentration and the bottomhole pressure in the annulus. The cuttings concentration increases as inclination angle of the well from the vertical increases for fixed gas and liquid injection rates (Fig.…”
Section: Effect Of Inclination On Bottomhole Pressure and Cuttings Comentioning
confidence: 99%
“…(6)(7)(8) illustrate the effect of well inclination on the cuttings concentration and the bottomhole pressure in the annulus. The cuttings concentration increases as inclination angle of the well from the vertical increases for fixed gas and liquid injection rates (Fig.…”
Section: Effect Of Inclination On Bottomhole Pressure and Cuttings Comentioning
confidence: 99%
“…Good cuttings transport ability of foam has been demonstrated in the field (Rojas et al, 2002), although formation of stationary cuttings beds has been reported by some experimental studies (Ozbayoglu et al, 2003;Martins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%